Dereplication by HPLC-ESI-MS and antioxidant activity of phenolic compounds from Banisteriopsis laevifolia (Malpighiaceae) - GERSO P. ALEXANDRE; JORGE LUIZ S. SIMÃO; MARIA OLIVIA A. TAVARES; IZABELLA MARIANA S. ZUFFO; STÉPHANIE V. PRADO; JOSEILSON A. DE PAIVA; ABUBAKAR N. MUSTAPHA; ANSELMO E. DE OLIVEIRA; LUCILIA KATO; VANESSA GISELE P. SEVERINO (Anais da Academia Brasileira de Ciências, 2021)
Abstract The genus Banisteriopsis (Malpighiaceae) comprises 77 genera and 1,300 species. Despite efforts to provide detailed information about the chemical wealth of B. laevifolia, this article provides the identification and characterization of compounds from the ethanolic extracts of the leaves and flowers using advanced methodologies which include high-performance liquid chromatography coupled to tandem mass spectrometry, which contribute to the knowledge about compounds present in the genus Banisteriopsis. The dereplication aided by Global Natural Products Social Molecular Networking afforded the identification of seven compounds reported for this species for the first time. A mixture of two known flavonoids and a diterpenoid, 18-hydroxy-ent-halima-1(10),13-(E)-dien-15-oic acid, were isolated by conventional separation methods. The elevated 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity observed in some samples was attributed to either the type of extract, the presence of 3,4,5-trihydroxybenzoic acid, or the influence of the substitution pattern and the synergistic effect of the compounds present. Principal Component Analysis was applied to correlate mass spectrometry data with the antioxidant activity of the samples. The high diversity of metabolites found in this study and those which have been reported for Banisteriopsis strongly recommends further investigation into the chemical and biological properties of these species.